Obtaining Callus Culture of Sage Medicinal (Salvia officinalis L.) and its Characteristics - N. S. Pivovarova; T. S. Shebitchenko; O. N. Abrosimova (Разработка и регистрация лекарственных средств)
Introduction. Cultivation of biomass of plant cells as a method of obtaining raw materials has existed for quite a long time. Plant cells cultivated in vitro act as a source of valuable secondary metabolites such as phenols, alkaloids, phytosteroids, glycosides, etc. It is important to create conditions under which the accumulation of valuable biologically active substances will be observed in the strains. Cultivation involves the use of complex multicomponent nutrient media containing a certain set of macro-, microelements, vitamins, growth stimulants. Salvia officinalis has a wide spectrum of pharmacological action. Due to the limited growing area of medicinal sage, as well as the deterioration of the ecological situation in the growing regions, the use of a phytobiotechnological method for obtaining raw materials is relevant.Aim. The aim of the study is to obtain a viable callus culture of salvia officinalis (Salvia officinalis L.).Materials and methods. Leaves of an intact plant sage medicinal, of the Lamiaceae family (Salvia officinalis, Lamiaceae) were used as explants. The explants were pre-sterilized with 6 % sodium hypochlorite solution for 20 minutes and 70 % ethanol for 1 minute. It was cultivated on a nutrient medium according to the Murasig – Skoog recipe. Determination of cell viability using vital dyes was assessed using microscopy (digital microscope Bresser LCD 50x-2000x, Germany). High performance thin layer chromatography was performed using a HPTLC PRO SYSTEM (CAMAG AG, Switzerland).Results and discussion. After two weeks of cultivation, the formation of primary callus was observed on the surface of the explants. Visually, it was a thin layer of intensely dividing undifferentiated light yellow cells. During cultivation, the biomass of the resulting callus increased, it became looser and acquired a darker shade, and the nutrient medium also began to darken. The detected cells during microscopy can be divided into two types: the first type is cells of the meristematic type, the second type is cells of the parenchymal type. Microscopy showed that more than 95 % of all visualized cells are alive. In the following passages, no significant changes in the morphotype of the culture were noted. In the eleventh passage, a study of the growth activity of the strain was carried out. The maximum specific growth rate of 0.42 day-1 is observed on the 14–18th day of growth, while the biomass doubling time is the smallest and corresponds to the value of 1.66 days. During one cultivation cycle, the amount of biomass increases by 7.73 times. The results of a qualitative analysis by the method of high-performance thin-layer chromatography (HTPLC) show that the qualitative composition of the biomass of medicinal sage is generally close to that of intact plants.Conclusion. A viable stable strain of plant cells of salvia officinalis was obtained on a nutrient medium according to the Murasig – Skoog recipe with a half content of micro- and macrosols and phytohormones 2,4-D (6 mg/ml) and kinetin (1 mg/ml). For the following passages, it is recommended to use a nutrient medium according to the Murasig – Skoog recipe with a full content of micro and macrosols and phytohormones naphthylacetic acid (1 mg/ml) and kinetin (1 mg/ml). The bulk of the obtained heterogeneous callus is made up of cells of the meristematic and parenchymal type. The qualitative composition of BAS biomass of medicinal sage is generally close to that of intact plants.